(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2025)
The COVID-19 pandemic, declared a public health emergency by the World Health Organization (WHO) on January 30, 2020, imposed mobility and socialization restrictions in several countries, affecting the daily lives of millions of people. As a result of these restrictions, many people spent more time in their homes, leading to an exponential increase in pet adoption rates. In addition, dogs already living with their guardians experienced an increase in the frequency of interaction, such as playtime, petting and short walks. This significantly changed the daily routines of the animals and led to changes in the lifestyles of the guardians, who adapted their care practices.